Diamantu podobne ogljikove (DLC) plasti - Čekada, Miha (Vakuumist, 2002)
Diamond-like carbon (DLC) is a common name for a metastable form of amorphous carbon with sizable content of spsup3 -bonds. It can contain up to 50 at.% of hydrogen. DLC thin films have some outstanding physical properties, such as high hardness, chemical inertness, low coefficient of friction and very low roughness. DLC films are applied as protective coatings for hard disk drives and for the protection of tools for dry machinning, while research on possible applications in various other fields is being conducted.
Keywords: ogljik; diamant; DLC; tanke plasti; lastnosti; uporaba